Coupling Sodium Dodecyl Sulfate–Capillary Polyacrylamide Gel Electrophoresis with MALDI-TOF-MS via a PTFE Membrane - Lu, Joann J. (2011)
Sodium dodecyl sulfate (SDS)–polyacrylamide gel electrophoresis (PAGE) is a fundamental analytical technique for proteomic research, and SDS–capillary gel electrophoresis (CGE) is its miniaturized version. Compared to conventional slab-gel electrophoresis, SDS-CGE has many advantages such as increased separation efficiency, reduced separation time and automated operation. SDS-CGE is not widely accepted in proteomic research primarily due to the difficulties in identifying the well-resolved proteins. MALDI–TOF–MS is an outstanding platform for protein identifications. Coupling the two would solve the problem but is extremely challenging because the MS detector has no access to the SDS-CGE resolved proteins and the SDS interferes with MS detection. In this work we introduce an approach to address these issues. We discover that poly(tetrafluoroethylene) (PTFE) membranes are excellent materials for collecting SDS-CGE separated proteins. We demonstrate that we can wash off the SDS bound to the collected proteins and identify these proteins on-membrane with MALDI-TOF-MS. We also show that we can immunoblot and Coomassie-stain the proteins collected on these membranes.